2019
DOI: 10.1016/j.ijfatigue.2019.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue strength of additively manufactured polylactide (PLA): effect of raster angle and non-zero mean stresses

Abstract: As far as polymers are concerned, polylactide (PLA) is certainly the polymeric compound that is most commonly used along with commercial additive manufacturing technologies. In this context, the present paper aims to investigate the influence of manufacturing direction and superimposed static stresses on the fatigue strength of PLA 3D-printed by using the Fused Filament Fabrication technique. This was done not only by generating a large number of new experimental results, but also by re-analysing different dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 21 publications
(49 reference statements)
0
23
0
Order By: Relevance
“…Table 3 shows a list of mechanical properties reported for FDM-produced PLA specimens (Ezeh and Susmel, 2019;Khan et al, 2018;Leite et al, 2018;Ouballouch et al, 2018;Tymrak et al, 2014;Wittbrodt and Pearce, 2015;Yao et al, 2019).Tensile strength values in the literature exhibit a very wide range of 19-58 MPa. While most of the data is somewhat close to the bulk strength of PLA, some of the studies reported much lower strength values.…”
Section: Polylactic Acidmentioning
confidence: 99%
“…Table 3 shows a list of mechanical properties reported for FDM-produced PLA specimens (Ezeh and Susmel, 2019;Khan et al, 2018;Leite et al, 2018;Ouballouch et al, 2018;Tymrak et al, 2014;Wittbrodt and Pearce, 2015;Yao et al, 2019).Tensile strength values in the literature exhibit a very wide range of 19-58 MPa. While most of the data is somewhat close to the bulk strength of PLA, some of the studies reported much lower strength values.…”
Section: Polylactic Acidmentioning
confidence: 99%
“…(B) Numerical results of the obtained von Mises stresses vs. applied load. (C) The endurance limit for ABS and PLA materials (Adapted from Caliskan et al, 2016 ; Ezeh and Susmel, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The orientation of the filament deposition during the process as well as the part build direction can also have major impact on mechanical characteristics of the AM parts [10,11]. It has been observed through various research studies that different AM plastic materials undergoing static or cyclic loadings behave differently with respect to the raster orientation.…”
Section: -Introductionmentioning
confidence: 99%